A pilot study of the Portuguese version of the Voices Acceptance and Action Scale: Psychometric properties in a clinical sample with psychosis-spectrum disorders - Martins, Maria João (2019)
Given the recent interest in acceptance-based interventions for psychosis, it has been recommended that coping with voices mechanisms, namely experiential acceptance, are routinely assessed in clinical and research settings. The Voices Acceptance and Action Scale (VAAS-12) is a self-report measure developed to specifically assess acceptance-based or action-based beliefs in relation to verbal auditory hallucinations. This study aimed to translate, adapt and study the psychometric properties of the Portuguese version of the VAAS-12 in a clinical sample within the psychosis-spectrum disorders. The VAAS-12 was translated and adapted to Portuguese. Its psychometric properties were then studied in a sample of fifty-four male participants, mostly single, unemployed, and with a last week voice hearing experience. Confirmatory analysis was performed for the one-factor and two-factor structure suggested for the VAAS in previous studies. Both had unacceptable fit indicators. Exploratory analysis then yield an alternative two-factor structure (“Non-interference and action” and “Acceptance and Life functioning” subscales) with adequate fit. Adequate internal consistency and construct validity were found, with the VAAS being negatively associated with perception of voices as hostile-dominant and resistance regarding voices. The VAAS-12 seems adequate to use in clinical and research studies, although further study is needed particularly regarding subscale “Acceptance and Life functioning”.